Dampak Berkendara di Bawah Umur terhadap Kejadian Kecelakaan Lalu Lintas pada Remaja di Indonesia - Sutrisno Syarifuddin; Mustakim Mahmud; M. Ibnu Sumarna; Muhammad Iqbal; Muh. Reza Zulfikar (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2026)
Traffic accidents (laka lantas) are a major safety issue in Indonesia, particularly those involving teenagers and minors as motorcyclists. This study aims to analyze the impact of driving without a driver's license (SIM) for those under 17 years of age on accident rates, casualties, and legal and social aspects. The methods used were literature study and secondary data analysis from the Indonesian National Police (Polri), Korlantas (Traffic Corps), and other official sources. The results show that in the first semester of 2025 alone, there were 133,811 child and adolescent drivers under 17 years of age involved in traffic accidents. The main factors include human error (high speed, not wearing a helmet, showing off skills), lack of parental supervision, and low risk awareness. The impacts include fatalities, serious/minor injuries, material losses, psychological trauma, and legal burdens for perpetrators and their families. This study recommends strengthening early road safety education, strict law enforcement, and the active role of parents and schools. Conclusion: Underage driving is not only a violation of Law No. 22 of 2009, but also has the potential to damage the future of the younger generation.